Effect of storage time and framework design on the accuracy of maxillary cobalt-chromium cast removable partial dentures - M Viswambaran; R K Sundaram (Wolters Kluwer Medknow Publications, 2015)
Statement of Problem: Inaccuracies in the fit of palatal major connectors may be related to distortion of the wax pattern due to prolonged storage time and faulty major connector design. Purpose: This in vitro study was carried out to find out the effect of storage time and major connector design on the accuracy of cobalt-chromium cast removable partial dentures (RPDs). Materials and Methods: A brass metal die with a Kennedy Class III, modification 1, the partially edentulous arch was used as a master die. Thirty-six refractory casts were fabricated from the master die. The refractory casts were divided into three groups (Group I: Anterior-posterior palatal bar, Group II: Palatal strap and Group III: Palatal plate) based on the design of maxillary major connector and subdivided into four groups (sub Group A: 01 h, sub Group B: 03 h, Sub Group C: 06 h, and sub Group D: 24 h) based on the storage time. For each group, 12 frameworks were fabricated. The influence of wax pattern storage time and the accuracy of the fit palatal major connector designs on the master die were compared. Casting defects (nodules/incompleteness) of the frameworks were also evaluated before finishing and polishing. Repeated measures analysis of variance was used to analyze the data. Results: The gap discrepancy was least in sub Group A (01 h) followed by sub Group B (03 h) and C (06 h) and most in sub Group D (24 h). Statistically significant differences (P < 0.05 in all locations L1-L5) in the fit of the framework were related to the design of the major connector. The gap discrepancy was least in Group I (anterior-posterior palatal bar) followed by Group II (palatal strap) and most in Group II (palatal plate). Conclusions: It is recommended that the wax patterns for RPD to be invested immediately on completion of the wax procedure. The selection of a major connector design is crucial for an accurate fit of RPD.